2009
DOI: 10.1177/039463200902200418
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide and Nitric Oxide Synthase Expression in Hodgkin's Disease

Abstract: Hodgkin's disease (HD) is a malignant lymphoma with frequent mediastinal involvement, characterized by a significant inflammatory infiltration. Exhaled Nitric Oxide (FENO), is present in healthy humans, and has been proven to be increased in eosinophilic diseases such as allergic asthma. We investigated whether FENO is increased in mediastinal HD and whether NO is produced by lymphoma tissue. To this aim FENO was measured in 56 HD patients, 17 with and 39 without bulky mediastinal involvement, in the period fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…eNO levels increase in patients with Hodgkin lymphoma and normalize following remission (13,14). A similar effect has been reported for patients with lung cancer, which exhibit increased eNO levels, including in our previous study (6,15).…”
Section: Discussionmentioning
confidence: 99%
“…eNO levels increase in patients with Hodgkin lymphoma and normalize following remission (13,14). A similar effect has been reported for patients with lung cancer, which exhibit increased eNO levels, including in our previous study (6,15).…”
Section: Discussionmentioning
confidence: 99%
“…16 -18 More recent studies found elevated FeNO levels in patients who were atopic but did not have asthma 6,19 and in nonatopic, nonasthmatic patients with Hodgkin's lymphoma. 20 Atopic dermatitis has also been associated with elevated FeNO levels. 11 These observations suggested a possible role for FeNO in immunologic diseases not restricted to the airways.…”
Section: Discussionmentioning
confidence: 99%
“…Although CANO is decreased in OSAS, overall FeNO is increased because the main component is produced by the upper airways [ 96 ]. Conversely, increased FeNO levels might reflect excessive vasodilation as in hepatopulmonary syndrome (HPS) [ 97 ] or be the consequence of a systemic high level of inflammatory cytokines as in Hodgkin's Lymphoma (HL) [ 98 ], systemic sclerosis (SSc) [ 99 ], Crohn's disease (CD) [ 91 ], and other inflammatory bowel diseases (IBDs) [ 92 ]. Perturbation of metabolism, such as in obesity, that leads to a proinflammatory condition may elevate FeNO as demonstrated by the correlation between body mass index (BMI) and FeNO [ 47 ].…”
Section: Nitric Oxide As a Mediator Of Inflammatory Diseasementioning
confidence: 99%